ANALISIS PENDIDIKAN KARAKTER, KERJA KERAS, MANDIRI, DAN TOLERANSI SISWA SD DIKECAMATAN RANTAU SELATAN KABUPATEN LABUHANBATU - Sonia Febryati; Rohana Rohana (STKIP Singkawang, 2022)
The aim of this study is to analyze the character education of elementary school students in the Rantau Selatan subdistrict in terms of hard work, independence, and tolerance. This descriptive qualitative research used five elementary school teachers in the Rantau Selatan district as subjects and gathered using the Slovin algorithm by the data students from elementary schools in Rantau Selatan district. Data collecting techniques include observation, interviews, and surveys. Data analysis is qualitative data analysis in accordance with Miles and Huberman's concept, namely data reduction, data presentation, and conclusion drafting. The percentage results indicate that 88% have demonstrated the ability to apply the character of hard work in order to foster an atmosphere of healthy competition; so, the results of this percentage are sufficient. in implementing the work ethic in the classroom. The results of teacher interviews indicate that a climate of healthy rivalry existed in the classroom, one of which included quizzes in addition to group discussions which indicated that 88 percent of students were able to apply the statement of responsibility for their actions, and the percentage results indicated that the independent character could be applied in the classroom. The percentage results for the character of tolerance indicate that 85% of elementary school students in Rantau Selatan district apply the statement about being able to forgive others' mistakes. Interviews with teachers revealed that in this case, the teacher always teaches students to forgive one another.